The Effect of Green Accounting Implementation and Leverage on Tax Avoidance in Mining Companies (2022–2024) - Dwi Pardosi; Herold Moody Manalu; Harlyn Lindon Siagian (Sean Institute, 2026)
This study aims to analyze the influence of green accounting and leverage on tax avoidance in mining companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The background of this study is based on the increasing public and regulatory attention to corporate environmental responsibility and corporate tax practices. This study employs a quantitative approach using secondary data obtained from companies’ annual financial reports and sustainability reports. The sampling technique utilized purposive sampling, resulting in 30 mining companies meeting the research criteria, with a total of 90 observations during the study period. Data analysis was conducted using multiple linear regression supported by descriptive statistics and classical assumption tests, including tests for normality, multicollinearity, and heteroscedasticity. The results indicate that green accounting and leverage do not significantly influence tax avoidance. These findings suggest that the implementation of environmental accounting practices and a company’s leverage level are not the primary factors influencing tax avoidance behavior in mining companies. Therefore, other factors such as profitability, firm size, and corporate governance likely play a more significant role in determining a company’s tax avoidance practices.